The Relationship Between Husband's Knowledge, Attitude and Support with The Behavior of Women for Early Detection of Cervical Cancer (Study Through Visual Inspection of Acetic Acid (VIA) - Siti Fitriah; Nia Kania; Triawanti Triawanti; Syamsul Arifin; Adi Nugroho (Lambung Mangkurat, 2023)
The death rate for cervical cancer in Indonesia is 8.2 deaths per 100,000 population. Meanwhile, the number of women with new cervical cancer is around 40 thousand cases each year. The purpose of this study was to determine the relationship between husband's knowledge, attitudes and support with the behavior of women of childbearing age conducting early detection of cervical cancer through visual inspection of acetic acid (VIA). This study uses a systematic review research design with meta-analysis. This study used the Meta-Analytic method with cross-sectional searches on the PubMed and Google Scholar databases. The publication bias test was carried out using a funnel plot while the statistical test used the Comprehensive Meta-Analysis version 3 (CMA version. 3). Based on the results of the study showed that of the 15 articles that met the CASP. There is a significant relationship between husband's knowledge, attitude and support with women of childbearing age behavior in carrying out early detection of cervical cancer through VIA. With pooled OR each of 3.518; 95% CI = 2.711- 4.564 for knowledge, 2.672; 95% CI = 2.085-3.457 for attitude and 3.930; CI 95% = 2.982-5.178 for husband's support. Husband's knowledge, attitude and support are significantly related to the behavior of women of childbearing age conducting early detection of cervical cancer through VIA